Endoscopic Papillotomy in Infancy Due to Biliary Cutaneous Fistula - N. ÖRMECİ,; A. ABASIYANIK,; M. BÜLBÜL,; H. AKA,; H. ATAYURT,; C. YURTAYDIN,; A. DÖKMECi,; Ö. UZUNALİMOĞLU, (Turkish Journal of Gastroenterology, 2020)
-